Metastatic Uterine Leiomyosarcomas: A Single-Institution Experience. Issue 2 (1st February 2010) - Bernstein-Molho, Rinat; Grisaro, Dan; Soyfer, Vjacheslav; Safra, Tamar; Merimsky, Ofer
Abstract : Background: Uterine leiomyosarcoma (LMS) is a rare disease and, when it recurs or metastasizes, can rarely be cured. In a retrospective study, we summarized our experience in treating a large cohort of patients with metastatic uterine LMS. Materials and Methods: Cases of recurrent or metastatic uterine LMS diagnosed between 2000 and 2008 were analyzed. Survival was determined from the time of initial diagnosis to last follow-up. Results: Thirty-three patients (median age, 55 years) were identified. Eighteen patients were initially diagnosed with localized disease. Median disease-free interval was 5.25 months, and overall survival (OS) is 43.7 months. Median OS of 15 patients with initially discovered metastatic disease is 31.4 months. Different chemotherapy regimens produced approximately 30% response rates. Twelve patients underwent at least 1 surgical resection of pulmonary or extrapulmonary metastases. In this group, median progression-free survival was 7.9 months (range, 0-33.9 months), median OS was 45.2 months (range, >8.1-78.8 months), 2-year survival rate was 83%, and 4-year survival rate was 25%. Conclusions: Very few patients with recurrent or metastatic uterine LMS can be curatively treated. Our experience suggests that modern multimodal therapy or combining chemotherapy with aggressive surgery in selected patients may be significant in prolonging survival of women with this fatal disease.